2014
DOI: 10.5455/ajvs.48232
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Blood Parameters, Immune response and Carcass Traits of Broiler Chicks Fed on Graded Levels of Wheat Instead of Corn without or With Enzyme Supplementation

Abstract: Broiler chicken Wheat grain Enzyme supplementation growth performance Immune response carcass traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
6
9
0
1
Order By: Relevance
“…These beneficial effects due to multienzyme application on lipid metabolites require further investigation. However, enzymes had no significant effect on concentrations of triglyceride and cholesterol compared with animals fed on the same diet without the addition of enzymes [46]. Similar to the current results, different blood cholesterols and HDL/LDL ratios were increased in the unsupplemented control groups than enzyme-supplemented groups, showing the positive influence of enzymes on blood cholesterol [7,41,47].…”
Section: Discussionsupporting
confidence: 82%
“…These beneficial effects due to multienzyme application on lipid metabolites require further investigation. However, enzymes had no significant effect on concentrations of triglyceride and cholesterol compared with animals fed on the same diet without the addition of enzymes [46]. Similar to the current results, different blood cholesterols and HDL/LDL ratios were increased in the unsupplemented control groups than enzyme-supplemented groups, showing the positive influence of enzymes on blood cholesterol [7,41,47].…”
Section: Discussionsupporting
confidence: 82%
“…However, rare articles reported improvement of immune organ weights with diets containing low-ME or enzyme supplementation. El-Katcha et al. (2014) reported that enzyme supplementation (Kemzyme Plus or COMBOzyme, AmericanBio., Inc., Natick, MA) to both wheat grain- and corn–soybean–based diets improved the thymus gland weight ( P ≥ 0.05) and relative weight compared with those of control without providing any explanation.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of protein and amino acid digestibility on growth may be associated to physical and chemical factors of the individual feed ingredients, as granule size and anti-nutritional factors (Romero et al, 2013;Amha et al, 2015). El-Katcha et al (2014) observed that performance index of broilers was not significantly affected by enzyme supplementation in comparison with the control group. In our trial, there was no difference in FCR between SD−P and SD+P treatments and this may be associated with optimal levels (Rostagno et al, 2011).…”
Section: Discussionmentioning
confidence: 98%